OZONESONDE MEASUREMENTS AT SYOWA STATION (69°00′S, 39°35′E) : PRELIMINARY RESULT - コンドウ, コウジ; イワサカ, ヤスノブ; スズキ, タケヒコ; カネト, ススム; KONDOH, Kouji; IWASAKA, Yasunobu; SUZUKI, Takehiko; KANETO, Susumu (National Institute of Polar Research, 1987)
P(論文) Ozonesonde measurements at Syowa Station (69°00′S, 39°35′E) from 1971 to 1984 showed that ozone depletion was most striking in the altitudinal region of 10 to 25km for the spring of the last five years. This ozone loss region corresponded to the region where a noticeable temperature drop was observed, also only in the spring, from 1981 to 1985. The comparison of the change in temperature field of the Antarctic stratosphere with that in the other regions suggests the possibility that the changes with a long time scale of about 10 years in the global-scale temperature field (and possibly with the dynamical systems in the stratosphere) are associated with the Antarctic ozone depletion in the last 10 years or so. departmental bulletin paper